PENGARUH LAMA PERENDAMAN CETAKAN ALGINAT DI DALAM LARUTAN DESINFEKTAN GLUTARALDEHID 2% TERHADAP STABILITAS DIMENSI - Eki Dyan Larasakti Santoso; Teguh Tri Widodo; Moh. Baehaqi (ODONTO : Dental Journal, 2014)
Background: Blood and saliva are the media for bacteria to accumulate, and it can stick to the surface of a alginate's impression during the molding process. Immersion with glutaraldehyde is one of the impression material desinfectant method since glutaraldehyde is spatially as bacterisid and fungisid. Something that must be considered when performing disinfection is the disinfection technique, as it would affect the dimension stability of impression materials. The aim of this research was to know the influence of immersion time in solution 2% glutaraldehyde disinfectant againts dimension stability. Method: The type of this research was quasi experimental using 30 samples, which were divided into five groups each containing 6 samples. The samples of alginate's impression were immersed in disinfectant solution of glutaraldehyde 2% respectively for 5, 10, 15, 20 minutes and also without immersion as the control group, then conducted a horizontal dimension stability measurement is the diameter of the die by using a digital caliper. Data were analyzed by one-way Anova test. Result: The result of this research were obtained a significance (p<0,05) between horizontal dimension stability of alginate's impression without immersed and horizontal dimension stability of alginate's impression after immersed for 5, 10, 15 and 20 minutes. Conclusion: Conclusion of this research was there was an influence of immersion time alginate's impression in disinfectant solution glutaraldehyde 2 % againts dimension stability.